THE DIGITAL MIND MAPPING ON WRITING SKILLS OF EXPLANATORY TEXTS IN ELEMENTARY SCHOOL - Saskia Azza Nabila; Ermawati Zulikhatin Nuroh (El Midad, 2025)
This study examines the effectiveness of digital mind mapping media on explanatory text writing skills. The subjects of this study were 25 sixth-grade students at SDN Sepande. Data collection in this study used quantitative pre-experimental data analysis techniques and data collection methods in pre-tests and post-tests to determine the effectiveness of digital mind mapping. Initial data collection in the form of a pre-test involved participants being directed to write explanatory texts on a predetermined topic, followed by a pre-test using digital mind mapping. The study's results showed an increase in students' writing skills during the study, as indicated by changes in the average scores obtained from the pre-test and post-test. The average score in the pre-test was 57.00, while the average score in the post-test was 82.80. Therefore, it can be concluded that sixth-grade students' explanatory text writing skills at SDN Sepande improved after using digital mind mapping.